Strategi Pemasaran Dengan Metode Potongan Harga Dalam Meningkatkan Minat Belanja - Rezky, Annisyah; Satriani, Satriani; Wanini, Wanini; Diva, Farah; Darniati, Darniati; Arifuddin, Arifuddin (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
This study aims to determine the marketing strategy of the Alfamidi Ahmad Yani Store in implementing discount or discount methods to increase consumer shopping interest in fulfilling their wants and needs. The technique used is qualitative by conducting direct research in the ﬁeld to observe the phenomena at Alfamidi Ahmad Yani to maximize the data obtained in marketing products that are given discounts and overcome problems or obstacles that arise during the research. Using this discount method positively impacts gaining proﬁt in-store revenue and can retain consumers. With this method, shops can also prevent losses due to non-sales of a product; for this reason, Alfamidi Ahmad Yani needs to maintain this strategy and develop price discounts for each product.